Comparison of inexperienced operators and experts in γH2A.X and 53BP1 foci assay for high-throughput biodosimetry approaches in a mass casualty incident. (2nd October 2020) - Bucher, Martin; Duchrow, Lukas; Endesfelder, David; Roessler, Ute; Gomolka, Maria
Abstract: Purpose: In case of population exposure by ionizing radiation, a fast and reliable dose assessment of exposed and non-exposed individuals is crucial important. In initial triage, physicians have to take fast decisions whom to treat with adequate medical care. In addition, worries about significant exposure can be taken away from hundreds to thousands non- or low exposed individuals. Studies have shown that the γH2A.X radiation-induced foci assay is a promising test for fast triage decisions. However, in a large-scale scenario most biodosimetry laboratories will quickly reach their capacity limit. The aim of this study was to evaluate the benefit of inexperienced experimenters to speed up the foci assay and manual foci scoring. Materials and methods: The participants of two training courses performed the radiation-induced foci assay (γH2A.X) under the guidance of experts and scored foci (γH2A.X and 53BP1) on sham-irradiated and irradiated blood samples (0.05–1.5 Gy). The outcome of laboratory experiments and manual foci scoring by 26 operators with basic experience in laboratory work was statistically analyzed in comparison to the results from experts. Results: Inexperienced operators prepared slides with significant dose-effects (0, 0.1 and 1.0 Gy) for semi-automatic microscopic analyses. Manual foci scoring by inexperienced scorer resulted in a dose–effect curve for γH2A.X, 53BP1 and co-localized foci. In addition, inexperienced scorers were able to distinguish low irradiation doses from unirradiated cells. While 53BP1 foci scoring was in accordance to the expert counting, differences between beginners and expert increased for γH2A.X or co-localized foci. Conclusions: In case of a large-scale radiation event, inexperienced staff is useful to support laboratories in slide preparation for semi-automatic foci counting as well as γH2A.X and 53BP1 manual foci scoring for triage-mode biodosimetry. Slides can be clearly classified in the non-, low- or high-exposed category.